The Locus Coeruleus Noradrenaline System in Delirium - Hansen, Niels; Rediske, Alina Isabel (Frontiers in Aging Neuroscience, 2021)
Delirium is a brain state involving severe brain dysfunction affecting cognitive and attentional capacities. Our opinion statement review aims to elucidate the relationship between abnormal arousal and locus coeruleus (LC) activity in cognitive dysfunction and inattention in delirium states. We propose (1) that enhanced noradrenaline release caused by altered arousal in hyperactive delirium states leads to increased noradrenergic transmission within the LC and subcortical and cortical brain regions including the prefrontal cortex and hippocampus, thus affecting how attention and cognition function. In hypoactive delirium states, however, we are presuming (2) that less arousal will cause the release of noradrenaline to diminish in the LC, followed by reduced noradrenergic transmission in cortical and subcortical brain areas concentrated within the prefrontal cortex and hippocampus, leading to deficient attention and cognitive processing. Studies addressing the measurement of noradrenaline and its derivatives in biomaterial probes regarding delirium are also covered in this article. In conclusion, the LC-NA system plays a crucial role in generating delirium. Yet there have been no large-scale studies investigating biomarkers of noradrenaline to help us draw conclusions for improving delirium’s diagnosis, treatment, and prognosis, and to better understand its pathogenesis.